The Health emergency management program of Ilocos Training and Regional Medical Center - Prepose, Norberto G. Jr. (San Fernando City, La Union : [s.n.], 2005)
This study aimed to propose measures to enhance the Health Emergency Management program of the Ilocos Training and Regional Medical Center.
Bibliography: pages 97-100.
CHED-La Union
Keywords: Health facilities